Validación de criterios ecográficos IOTA (International Ovarian Tumor Analysis Group) para caracterizar masas anexiales y determinar riesgo de malignidad en un grupo de mujeres con sospecha de cáncer de ovario - Preisler R., Jessica; Burgos S., Nelson; Cisternas O., Daniela; Gayan P., Patricio; Chávez R., Ignacio; Aleuanlli A., María Cristina; Bustos S., Carolina; Barros B., Antonia; Hurtado T., Iván (Revista Hospital Clínico Universidad de Chile, 2017)
Epithelial carcinoma of the ovary is a gynecological malignancy associated with high mortality rate due to diagnosis in advanced stages, which occurs in more than 75% of the cases. Recent strategies in reducing mortality have been studied, however screening tests have not demonstrated to help in the diagnosis at early stages. Subjective impression of the examiner using transvaginal ultrasound is considered the best method to discriminate between benign and malignant adnexal tumors. The International Ovarian Tumor Analysis Group (IOTA) based on ultrasound features of the adnexal masses, has developed robust rules and prediction models that can be used by different examiners in various clinical settings.In Chile during 2012, national guidelines about epithelial ovarian cancer were published, establishing referral and management criteria. Little mention about ultrasound exam was included: all “solid tumors or complex adnexal masses” are sonographic criteria to refer patients to gynecologic oncology units. Considering that many functional or benign pathologies can be classified as “complex tumors”, it is important to use validated prediction models to improve accuracy of ultrasonography and therefore optimize the referral to gynecological oncologists and avoid surgeries of misclassified adnexal pathologies.